Improving equity and access to buprenorphine treatment through telemedicine at syringe services programs - Barrot H. Lambdin; David Kan; Alex H. Kral (Substance Abuse Treatment, Prevention, and Policy, 2022)
Abstract Background and aims In the United States, access to buprenorphine remains low and disparities regarding who receives treatment have emerged. Federal laws have regulated buprenorphine delivery, ultimately limiting its implementation more broadly. At the onset of the COVID-19 pandemic, federal agencies acted quickly to remove a legal barrier, effectively allowing people with opioid used disorder (OUD) to initiate buprenorphine treatment via telemedicine. Leveraging this policy shift, a low barrier buprenorphine treatment initiative via telemedicine was started at syringe service programs in California. We assessed early findings from participants reached by this model of treatment. Methods In May 2020, buprenorphine treatment was offered through a virtual platform to SSP participants in California. SSP staff connected interested participants to virtual appointments with medical providers in a private location. During these visits, clinicians conducted clinical assessments for diagnosing participants with OUD and developed an unsupervised home induction plan for individuals who were eligible. Participants were prescribed a 7-day supply of up to 16 mg daily buprenorphine or 16 mg buprenorphine-2 mg naloxone and asked to return the following week if interested in continuing treatment. Results From May 2020 to March 2021, the SSP-buprenorphine virtual care initiative inducted 115 participants onto treatment with 87% of participants inducted on the same day as their referral. Of those inducted, 58% were between the ages of 30 and 49 and 28% were cisgender female. Regarding participants’ method of payment to reimburse buprenorphine costs, 92% of participants were covered by Medicare/Medicaid. Overall, 64% of participants returned for a second buprenorphine prescription refill. Conclusions These early findings suggest that this could be a promising approach to improve equity and access to buprenorphine treatment. We encourage policymakers to continue allowing buprenorphine delivery via telemedicine and researchers to study whether this approach improves equity and access to treatment throughout the United States.